Growth Dynamics and Sustainability of Major Crops in Haryana, India - Bagaria, Nidhi; Jatav, Surendra Singh (Indian Journal of Extension Education, 2025)
The study examined the nexus between crop growth, instability, and groundwater depletion in Haryana, India. Data was collected during 2022 to first examine the trends of cropped area, production, and productivity by calculating compound annual growth (CAGR). The drivers of crop growth and instability in area, production, and productivity using decomposition analysis and the Cuddy-Della Valle Instability index, were examined respectively. Finally, the Pearson and Spearman correlation methods to investigate the relationship between groundwater depletion and crop yield were employed. Consistent production growth in wheat and rice but negative growth in gram and cotton production observed. After 2015, bajra and rapeseed-mustard showed big improvements, indicating success of programs like "Mera Pani Meri Virasat" that encourage water-efficient farming. Instability analysis indicated low variability in wheat and rice yields but high instability in sugarcane and gram. Gram's resistance to low water levels and rice's strong reliance on groundwater were both brought to light by correlation analysis. The findings stress the importance of crop diversification, especially promoting gram production, and suggest targeted interventions in yield enhancement for sustainable agricultural development.